Analisis Karakteristik dan Tingkat Hambatan Samping Ruas Jalan D.I. Panjaitan Kota Kendari - Amir, Andi Ahdan; Arsyad, Muhammad; Sukman, Sukman; Diansar, Diansar (FROPIL (Forum Profesional Teknik Sipil), 2023)
Progress inland transportation has not escaped the emergence of new problems from environmental aspects, accidents, and congestion. Traffic congestion occurs due to the imbalance between the growth of vehicles with improved infrastructure, rapid urbanization, low of discipline of road users, and side friction. Land use, type of road, and size of the city result in the characteristics and level of side friction. From these things, research on the analysis of characteristics and level of side friction on the D.I. Panjaitan Road section of Kendari City became interesting. The purpose of this study is to identify the characteristics of side friction and determine the level of side friction. From research and analysis, it was found that side friction that occurs at three observation points is generally caused by the type of activity of stopped vehicles, parking on street, and vehicles come into and exit from the parking area and coming into or leaving the neighborhood. Based on side friction frequency data at three observation points showed the lowest Side Friction Frequency (SFF) of 33.5 and 39.4 events at point T3, then 67.6 and 64.4 at point T2, and the highest at point T3 70.5 and 59.9 events. The data shows that the side friction class on the road is categorized is very low. The low side friction at the observation location is caused by the observation time carried out during the decline in community activities due to the implementation of health protocols due to the increase in Covid-19 cases